2022
DOI: 10.3389/fimmu.2022.907994
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of NK Cell Phenotype During Pregnancy in Multiple Sclerosis

Abstract: In multiple sclerosis (MS), relapse rate is decreased by 70-80% in the third trimester of pregnancy. However, the underlying mechanisms driving this effect are poorly understood. Evidence suggests that CD56bright NK cell frequencies increase during pregnancy. Here, we analyze pregnancy-related NK cell shifts in a large longitudinal cohort of pregnant women with and without MS, and provide in-depth phenotyping of NK cells. In healthy pregnancy and pregnancy in MS, peripheral blood NK cells showed significant fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Although this cohort offers a valuable opportunity to gather preliminary insights, another limitation is represented by the variable sampling time in pregnant mothers. As reported by Wisgalla A et al, in healthy pregnancy peripheral blood, NK cells showed an increase in CD56bright and a decrease in CD56dim populations toward the third trimester [42]. In our cohort, CD56dim population frequency was not affected by third trimester sampling.…”
Section: Discussionsupporting
confidence: 82%
“…Although this cohort offers a valuable opportunity to gather preliminary insights, another limitation is represented by the variable sampling time in pregnant mothers. As reported by Wisgalla A et al, in healthy pregnancy peripheral blood, NK cells showed an increase in CD56bright and a decrease in CD56dim populations toward the third trimester [42]. In our cohort, CD56dim population frequency was not affected by third trimester sampling.…”
Section: Discussionsupporting
confidence: 82%
“…No concordant or discordant evidence of these findings can be found in the literature. However, Wisgalla et al [ 15 ] showed that percentage levels of NK cells increase during pregnancy of MS patients while decreasing significantly in the postpartum period [ 15 ]. Based on the assumption that pregnancy is protective against disease activity while postpartum increases the risk of MS reactivation [ 16 ], our data would be in line with the literature, confirming the protective effect of a higher percentage of NK cells on MS.…”
Section: Discussionmentioning
confidence: 99%
“…In women with MS, the NK cells are reversed postpartum [80]. Pregnancy was found to promote the marked transformation of NK cells into a regulatory CD56 bright NK cell population that expressed receptors associated with cytotoxicity (such as the CD16 + NKp46 high NKG2D high NKG2A high phenotype) [80]. ULBP4 was found to be predominantly expressed by astrocytes rather than neurons [81].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%